Unilateral striatal CT and MRI changes secondary to non-ketotic hyperglycaemia. (2nd May 2014) - Johari, Bushra; Hanafiah, Mohammad; Shahizon, Azura Mohamed Mukhari; Koshy, Marymol
Abstract : A 62-year-old man presented with a right-sided hemichorea-hemiballismus secondary to underlying non-ketotic hyperglycaemia. This condition is recognised to have a unique finding of unilateral basal ganglia lesion, which is hyperdense on CT and hyperintense on T1-weighted MRI. The clinical course of this condition is benign and has a good prognosis with early correction of the hyperglycaemia.